Effects of germination on nutritional properties and anti-nutrients in selected legumes - Megat Radzi, Megat Rusydi (2015)
Legume is a plant in the family of Fabaceae (or Leguminosae) that is cultivated and consumed throughout the world. Legume’s role in human health appears to be limited because of several limiting factors such as low protein and starch digestibility, poor mineral bioavailability and high anti-nutritional factors. Germination is defined as a process that occurs during seed growth that starts with uptake of water until the emergence of radicle through the surrounding structure. It has been suggested that germination is a cheaper and more effective technology that can improve the quality of legumes by increasing their nutritional value. This study is conducted to compare changes in proximate content, anti-nutrients, anti-oxidants, dietary fibre, total sugar and fatty acid composition after germination process in kidney, mung, soy beans and peanuts. Germination was done by soaking the legume samples followed by leaving the samples on wet muslin cloth until the emergence of radicle. Germination caused a significant increase (p<0.05) of moisture content while ash, carbohydrate, protein and fat contents were significantly decreased. Total dietary fibre (both soluble and insoluble) was found to be significantly increased (p<0.05) in all germinated legume samples. Tannin content in germinated mung beans and peanut was decreased while phytic acid of germinated mung and soy beans was significantly decreased (p<0.05). Total cyanide content was significantly decreased (p<0.05) in all germinated legumes. All germinated legumes had significantly lower (p<0.05) total phenolic content while ferric reducting ability of plasma (FRAP) level was increased in all except germinated peanuts. Diphenyl-1-picrylhydrazyl (DPPH) activity of germinated mung beans was improved while in other germinated legumes, it was reduced. For fatty acid composition, saturated fatty acids was decreased in germinated soy beans and peanuts while polyunsaturated fatty acids was increased in germinated peanuts. For total sugar content, germination increased the level in all legume samples. Overall, germination has been proven to improve nutritional properties of legumes but the changes are influenced by the type of legumes.